Pelatihan Latihan Berpikir Positif Giat Bullying (Bahagia Tanpa Bullying) Sebagai Upaya Pencegahan Perilaku Bullying Pada Remaja - Riska Amalya Nasution; Meinarisa Meinarisa; Kamariyah Kamariyah; Yuliana Yuliana; Putri Irwanti Sari; Ilham Falani (I-Com: Indonesian Community Journal, 2024)
Bullying is a serious problem among adolescents today. The impact of bullying on adolescents is very broad, including mental health problems such as depression, anxiety, and low self-esteem. GIAT Bullying (Happy Without Bullying) is a community service program designed to provide positive thinking training to adolescents as an effort to prevent bullying behavior. This program recognizes that bullying is a serious problem that can affect the psychological and emotional well-being of adolescents. Therefore, through a series of trainings and workshops, this program aims to equip adolescents with the skills and knowledge needed to deal with, prevent, and stop bullying. Positive thinking training, as the core of this program, is aimed at helping adolescents develop a healthy and positive mindset, which in turn can minimize their risk of becoming victims or perpetrators of bullying. Community service activities were carried out at SMPN 21 Tanjung Jabung Timur in September 2024 with the results of the community service showing an increase in the ability of teenagers to carry out positive thinking exercises and an increase in knowledge about bullying. Thus, GIAT Bullying makes an important contribution to creating a safe and supportive environment for adolescents, where they can grow and develop without fear or threat of bullying.